Capability deployment in crisis response to Asia tsunami disaster - PAN, Gary (Institutional Knowledge at Singapore Management University, 2013)
The case covers the Asian tsumani in 2004 and the management of the crisis relief operations. The United Nations proposed a regional coordination centre in Singapore to coordinate all relief activities in the region. Singapore was considered the ideal candidate to coordinate the relief activities, due to its proximity to a number of tsunami-hit countries, her well-developed communications and logistics networks, and her status as a medical hub in the region.